Pengaruh Empati dan Etika Perwira terhadap Keselamatan Kerja Kru Kapal Pada Industri Pelayaran - Wiyono, S Teguh; Kuncowati; Daryanto, Daryanto (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
This study aims to analyze the influence of ship officers' empathy and ethics on occupational safety in the shipping industry. Data were collected from 60 respondents consisting of ship officers from national shipping companies. The research instrument used a structured questionnaire with a 5-point Likert scale. Data analysis was performed using SPSS version 26, including validity tests, reliability tests, multiple linear regression, and hypothesis testing. The results indicate that officers’ empathy has a positive and significant effect on work safety by 47.6%, while officers’ ethics contribute 36.0% positively and significantly. Simultaneously, empathy and ethics together influence occupational safety in the shipping industry by 49.4%. These findings highlight the importance of fostering empathy and ethics in shaping a safety culture onboard ships.